Cutaneous presentation of progressive disseminated histoplasmosis nine years after renal transplantation. Issue 2 (6th February 2013) - Rosado‐Odom, V.M.; Daoud, J.; Johnson, R.; Allen, S.D.; Lockhart, S.R.; Iqbal, N.; Shieh, W.‐J.; Zaki, S.; Sharfuddin, A.A.
Abstract Initial presentation of invasive fungal infections such as histoplasmosis can include non‐specific clinical manifestations, especially in immunocompromised patients. A high index of suspicion is required to identify atypical manifestations of these diseases, which carry a high risk of mortality, if the diagnosis is delayed or missed. We describe a case of a kidney transplant recipient with cutaneous lesions as initial manifestation of progressive disseminated histoplasmosis where a skin biopsy was crucial to an early diagnosis.